Global Research Trends on Learning Technology in Psychology: A Bibliometrics Analysis - Jailani, Mohammad; Mahanani, Sari; Veronika Moruk, Selviana (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
The urgency of this research stems from the growing use of learning technology in psychology, particularly since the COVID-19 pandemic accelerated the adoption of remote and technology-based learning. Although numerous studies have been conducted, the understanding of global trends in this topic remains limited. This study aims to analyze global trends related to learning technology in psychology using bibliometric methods. The methodology employed in this research is bibliometric analysis, using VOSviewer software to map prominent topics frequently discussed in academic literature from 2004 to 2024. The findings reveal that deep learning, self-efficacy, social relationships, and the impact of COVID-19 are dominant themes within learning technology in psychology. Additionally, a significant increase in publications and citations on this topic has been observed over the past two decades. The study also identifies six main clusters that illustrate interconnections among themes. In conclusion, learning technology is increasingly vital in educational psychology, particularly in student motivation, engagement, and performance. This research comprehensively maps global trends in learning technology within psychology. It identifies opportunities for further study, particularly regarding the impact of technology in the post-pandemic era.